Ethics, Prerequisites, and Limitations of the Translator (Culture, Art, and Texture based on the Book of Essays and Rules of Translation Industry by Hesamuddin Mostafa) - Fatemeh Dini; Javad Asghari (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2022)
Each profession has its own rules, limits, and restrictions, and for each profession, its boundaries and rules must be defined. Adherence to the standards, values, and limitations of each discipline can be defined as the professional ethics of that discipline. Due to the special position of the translator in the translation process, the present article has tried to express the ethics of the translator's profession and the prerequisites of the translation profession while using the descriptive-analytical method. Understanding the prerequisites and challenges and slips of the translation profession, as well as work experience in specific fields, makes the translator specialize in a field of translation techniques, and the process of finding expertise provides an important part of professional ethics in the field. Hussam al-Din Mustafa in his book "Basics and rules of the translation industry" has referred to the subject of professional ethics of translation and to various issues in this field, which is the basis of this article. The authors have come to the conclusion that: Familiarity with the culture of the source language, specialization in translation, familiarity with the technique of translation, context in translation, and translation process, are the most important prerequisites that a translator should consider, to be able to provide a more acceptable translation.